O manicômio judiciário e seus pacientes na visão dos trabalhadores: atenção à saúde e equipamento prisional - Ana Flavia Ferreira de Almeida Santana (2015)
The reality of a Hospital of Custody and Treatment (HCT), previously called as judiciary asylum, as a structured whole of which society used to handle with the madness related to criminality was the target of this study. The construction and maintenance of this institution, comprehended in its historical and organizational aspect, including actions of health and security professionals, were approached by the relation between means and instruments established and used. The HCT is an institution in charge of enforcing the treatment and charged with deprivation of freedom the mental suffering ones under security measure. This study had the objective to analyze the contradictions in a Hospital of Custody and Treatment, focusing on its health care function and public security. The option by the dialectic historical materialism had as fundament the theoretical possibility of being used as an instrument for the interpretation of the reality. With its inherent logical essentiality, the dialectic showed a path to the comprehension and consequent possibility of transformation of HCTs reality. The study scenario HCT Jorge Vaz, located at Barbacena city, MG, Brazil. This is the only states judiciary asylum, built in 1927. The collect of data was conducted using three different techniques, aiming the information crossing, that is, Documental Analysis, Interviews and Observation. The sample was for convenience and the professionals of HCT and judges of Criminal Courts and Criminal Execution of Minas Gerais. The interviews were subjected to content analysis and documents and observations used to complement the information as a way of apprehension the internal connections, seeking for a global vision and the contradictions that exists. The results show that prevails the vigilance by the security agents, at the expense of the healthcare attention, despite having a multi-professional team; there is few or no action toward the social reinsertion of the interns and has lack of people, medicines and other means and instruments to attend the needs of the people at Security Measure. The parameters for the treatment of the patients are established by each professional, individually, according to his perception of the interns and world view. There is no team work and is not followed what is recommended by the Health Unique System and by the specific laws for mental health. There is no training to work at HCT and the security agents are trained to work in ordinary prisons. It may be concluded that the objective proposed by the Security Measure, to be put on practice by the institution, has not been reached, remaining the same prey to the past practices. The focus at HCT is not the treatment or the care, but the constant surveillance and the maintenance of the socially undesirable subject locked up and stabilized and with no condition to compromise the social order.